Experimental and numerical investigation of single-phase hydrodynamics in glass sponges by means of combined µPIV measurements and CFD simulation. (16th March 2017) - Meinicke, Sebastian; Möller, Christian-Ole; Dietrich, Benjamin; Schlüter, Michael; Wetzel, Thomas
Abstract: The following paper presents a combined experimental and numerical approach to analyze single-phase hydrodynamics inside porous SiO2 glass sponges (=open-cell foams). For this purpose, a µPIV method has been applied to visualize instantaneous velocity fields of refractive index-matched aqueous Dimethyl sulfoxide (=DMSO) solution flow through the voids of the complex, irregular structure. Results have been recorded for a superficial flow velocity range from 0.02 to 0.38 m/s (corresponding to Reynolds number values between 30 and 650), covering – according to available classifications in literature – all distinguished flow regimes inside such porous systems. µPIV data is used to substantiate the existence of different flow regimes in irregular porous media, to detect their particular flow characteristics and to track the transition points between the prevailing flow regimes. Furthermore, µPIV data has been time-averaged and compared to corresponding numerical results of a laminar, steady-state CFD modelling approach, which is based on reconstructions of the real sponge geometry gained from X-ray tomographic scans of the structure. Experimental and numerical results of pore-scale velocity fields have been compared at three different measurement positions and show good agreement in terms of observed flow structure and direction as well as magnitude of the respective mean velocity fields. Highlights: Recording of pore-scale resolved velocity fields in SiO2 glass sponge structures. Distinguishing and characterization of different flow regimes prevailing in sponges. Evaluation of corresponding µPIV and CFD data at different measurement positions. In-depth analysis of 2-D contours and 1-D courses of recorded local velocity fields. Judging the current CFD approach's suitability to model hydrodynamics in sponges.